Traumatic avulsion fracture of the lesser trochanter in a dog - Vidoni, B.; Henninger, W.; Lorinson, D.; Mayrhofer, E. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
A 15-month-old 25 kg female spayed American Staffordshire Terrier was examined to determine the cause of a six month period of lameness of the left pelvic limb. Signs of severe pain were evident on hyperextension and simultaneous internal rotation or abduction of the left hip joint; crepitus or instabiltiy was not detected. The diagnosis of avulsion fracture of the lesser trochanter was based on radiographs, computed tomography (CT) and magnetic resonance imaging (MRI), supported by initial findings such as lameness and hip joint pain in extension. The dog was treated with strict confinement for eight weeks followed by a gradual increase in activity; non-steroidal anti-inflammatory drugs were given for one month. Three months later, the dog was clinically sound and unrestricted activity was resumed. Soundness was confirmed on follow-up 18 months after injury. CT and especially MRI were powerful diagnostic tools to identify chronic iliopsoas strains with an avulsion fracture of the lesser trochanter. Complete recovery ensued following conservative treatment only, despite the proximal diplacement of an avulsed segment of the lesser trochanter. Thus, traumatic injury to the iliopsoas muscle and to the lesser trochanter should be included as differential diagnosis in cases of hind leg lameness.
Keywords: Dog; avulsion fracture; lesser trochanter; magnetic resonance imaging (MRI); computed tomography (CT)